A Critical Review On Ruellia Tuberosa, Saccharum Benghalense And Dichanthium Annulatum With Huge Availability In ‘Middle Ganga Segment’ (Journal of Pharmaceutical Negative Results, 2023)
One of the most significant sources of medications comes from plants. Plants have been used as remedies from the prehistoric era. This review was based on the chemical investigation and pharmacological evaluation of some medicinal plants i.e., Ruellia tuberosa, Saccharum benghalense and Dichanthium annulatum found in middle ganga segment. This review consists an extensive survey of literature from the Scopus/PubMed, Google Scholar, and other international reputed sources. The plant Ruellia tuberosa belongs to the Acanthaceae family and was introduced as a decoration to an Indian garden. It is a native of Central America. It has been employed in traditional medicine as a diuretic, antidiabetic, antipyretic, analgesic, and anti-hypertensive, as well as a quencher of thirst and an antidote. Saccharum benghalense is synonym for Tripidium bengalense that is also called as munj grass that grows in desert regions and along river banks. It is native to Myanmar, Bangladesh, Nepal, Afghanistan, Pakistan, northern India, and Iran. In the form of a solution or a powdered mixture, the plant's barks, leaves, roots, fluids, gums, fruits, and seeds are used to cure a variety of illnesses including fever, inflammation, bleeding wounds, burning sensations and herpes etc. Dichanthium annulatum belongs to Poaceae (Graminae) family. This review leads to the conclusion that the nutritional components of Saccharum munja, which include sodium, potassium, calcium, magnesium, chloride, bicarbonates, iron, phosphate, and sulphate, are what give the plant its medicinal value.